2011
DOI: 10.1111/j.1752-9824.2011.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

The process of medication management for older adults with dementia

Abstract: kaasalainen s, dolovich l, papaioannou a, holbrook a, lau e, ploeg j, levine m, cosby j & emily a (2011) Journal of Nursing and Healthcare of Chronic Illness 3, 407–418 
The process of medication management for older adults with dementia Aim.  The purpose of this study was to explore the personal experiences related to medication management of community‐dwelling older adults diagnosed with dementia, their informal caregivers, as well as healthcare professionals who assist them. Background.  Older adults who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 39 publications
6
83
2
Order By: Relevance
“…Subsequently, in a qualitative study conducted by Kaasalainen et al . (), the following strategies were suggested as being useful: establishing medication routines, using dose administration aids, hiding medication in foods, simplifying dosage regimens and using liquid oral medications (where possible) to improve medication compliance.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, in a qualitative study conducted by Kaasalainen et al . (), the following strategies were suggested as being useful: establishing medication routines, using dose administration aids, hiding medication in foods, simplifying dosage regimens and using liquid oral medications (where possible) to improve medication compliance.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, caregivers indicated that they were “on duty” for much of the day. Given these findings along with the frailty of the patients and the number of medications that patients were taking, our caregivers demonstrated that medication management, when patients have memory loss, is burdensome and complicated by the patient’s physical, behavioral, and cognitive problems supporting work by Kaasalainen et al (2011).…”
Section: Discussionmentioning
confidence: 97%
“…When caregivers trust that patients are taking their medications correctly, they exert little, if any, control over that situation. Similarly, Kaasalainen and colleagues (2011) found that the severity of the patient’s dementia influences medication management. Research is needed to more comprehensively address the complex nature of medication management in patients with cognitive decline and support the theoretical basis for interventions (Banning, 2009).…”
mentioning
confidence: 96%
“…The discrepancy in domains reported as problematic in the studies may be due to different assessment scales or scoring procedures of IADL. The information of disability in the items shopping, food preparation and responsibility for own medication in our study is interesting since malnutrition and compliance regarding medication are often reported among elderly people with dementia [32,33]. …”
Section: Discussionmentioning
confidence: 99%